Perfil dos pacientes com tuberculose em tratamento e o nível de satisfação do atendimento em um centro de saúde de Fortaleza : proposta para desenvolvimento de um serviço de farmácia clínica - Silva, Erika Lizette Silveira da (2009)
TB has a long-term complex treatment and involves the association of various drugs. The rate of treatment abandonment is high and can lead to the appearance of resistant forms of M. tuberculosis. The World Health Organization recommends the implementation of the Directly Observed Treatment Short Course – DOTS, as a strategy for the detection of new cases and for achieving the completion of TB treatment. In Brazil, the Family Health Program expanded the access of the patient to health care, facilitating the follow-up of his treatment and case detection. The TB control also depends on the government management in order to make available national programs for case active searching, treatment adherence, intervention in risk groups, information accessibility, epidemiological surveillance. However, the state-of-the-art of the TB treatment reveals that it is still insufficient what is being done for the disease control. In this aspect, our work aims to get subsidies for the proposal of a service establishment model in Clinical Pharmacy. OBJECTIVES: To evaluate the profile of tuberculosis patients under treatment and their level of satisfaction with the service in the Health Center Carlos Ribeiro, from January to December, 2007. METHODS: Descriptive, observational, transversal study of TB patients in treatment at the Health Center Carlos Ribeiro, Fortaleza. RESULTS: The main findings were that among patients, 32.5% were female and 67.5% male. The ages ranged from 12 to 81 years and the age of 12 to 25 (33.3%), 26 to 35 (20.5%), 36 to 45 (24.4%), 46 to 55 (12.8%) and 56 to 65 years (9.0%). According to school graduation, 21.7% were illiterate, 16.9% had studied for 1 to 3 years, 22.9%, for 4 to 7 years, 38.6% more than 7 years. In respect to the job issue, 39.8% were informally employed and 60.2% were unemployed. In respect to the housing, most of them had water supply (88.0%), but few had water drainage (31.3%). Thirty four percent of the houses were poorly ventilated and had 1 to 3 rooms, with 5 to 11 people per residence. In respect to the disease knowledge, 34.9% of the patients were not aware of which kind of disease TB was, and 41,0% did not know how the TB transmission could occur. In respect to the microbiological monitoring during treatment, few have done the whole schedule. In respect to drug adverse reaction, 77.1% have complained about at least one adverse event during the treatment. In respect to completion of the treatment, only 71.1% have concluded it; the others have abandoned it. CONCLUSION: The patients, mostly of the male gender on productive age, presented similar profile compared to other studies, with low graduation rates, alcoholism and smoking habits, unemployment. It has been observed that a percentage of that population had no knowledge about the disease and its treatment. It was also observed that the quality of patient care was considered inadequate. Procedures such as monitoring and microbiological monitoring of adverse reactions had not been conducted. Maybe so, it noted a higher rate, and consequently a lower rate of cure.Anyhow, the study could achieve its goal, that is, to offer subsidies for a future strategy planning model for the follow-up of the TB patient considering Clinical Pharmacy.